Analisis Pemasaran Ikan Bandeng Di Desa Pitue Kecamatan Maâ€™rang Kabupaten Pangkep - Nurdiana, Nurdiana (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
The purpose of this study to determine the pattern of marketing channels, marketing margin and the level of marketing efficiency Pitue fish in the Village, District Ma'rang Pangkep. This research uses descriptive method. The analysis used data analysis techniques and marketing agency channel, analysis of market behavior, marketing margin analysis, analysis of the share of farmers and marketing efficiency analysis. The results showed fish marketing channels is the marketing channel (milkfish aquaculture farmers, traders, retailers, end consumers) and II (pond fish farmers, retailers, consumers end), which is the most efficient channel marketing II. Marketing margins in the channel I is greater than the margin of marketing channels II. Marketing of fish in the pitue village districtÂ  ma'rang Pangkajene archipelago efficient, because the value of marketing efficiency of marketing channels I and II was 11.52 per cent and 7.10 per cent less than 50 per cent